2019
DOI: 10.1093/jas/skz258.816
|View full text |Cite
|
Sign up to set email alerts
|

PSXII-11 In vitro fermentative parameters of diets containing increasing inclusions of soybean molasses for sheep

Abstract: The objective of this study was to evaluate the effects of increasing inclusion of soybean molasses (SM) in sheep diets on in vitro gas production, pH, N-NH3 and VFA. Three ruminally-cannulated adult sheep were used as donors of inoculum. The treatments consisted of diets containing 0, 10, 20 and 30% of SM (DM basis) with forage: concentrate ratio of 20:80. The experimental design was completely randomized with repeated measurements over time (2, 6, 12 and 24 hours). Flasks with a volume of 50 mL were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… Arruda et al (2021) and Rodrigues et al (2020) evaluated SM inclusions of up to 30% in the DM of the diet and observed no effects on lamb feed intake and performance. Previous reports indicate that SM-containing diets have a higher digestibility ( Pereira Junior et al, 2018 ; Arruda et al, 2019 ), an effect that may be attributed to the carbohydrate solubility that SM adds to the diet (35.1—CON vs. 230.8 g kg -1 SM20 of soluble carbohydrates). However, it is worth noting that these studies were based on in vitro assays, which for diets with SM do not represent the most accurate method for estimating digestibility.…”
Section: Discussionmentioning
confidence: 99%
“… Arruda et al (2021) and Rodrigues et al (2020) evaluated SM inclusions of up to 30% in the DM of the diet and observed no effects on lamb feed intake and performance. Previous reports indicate that SM-containing diets have a higher digestibility ( Pereira Junior et al, 2018 ; Arruda et al, 2019 ), an effect that may be attributed to the carbohydrate solubility that SM adds to the diet (35.1—CON vs. 230.8 g kg -1 SM20 of soluble carbohydrates). However, it is worth noting that these studies were based on in vitro assays, which for diets with SM do not represent the most accurate method for estimating digestibility.…”
Section: Discussionmentioning
confidence: 99%